Back Cover: Tailoring Phase Alignment and Interfaces via Polyelectrolyte Anchoring Enables Large‐Area 2D Perovskite Solar Cells (Angew. Chem. Int. Ed. 36/2022). Issue 36 (26th July 2022) - Han, Chenxu; Wang, Yao; Yuan, Jiabei; Sun, Jianguo; Zhang, Xuliang; Cazorla, Claudio; Wu, Xianxin; Wu, Ziang; Shi, Junwei; Guo, Junjun; Huang, Hehe; Hu, Long; et al.
Abstract : An efficient polyelectrolyte hole‐transport layer was explored for 2D perovskite solar cells by using a compatible butylamine cation, as reported by Jianyu Yuan and co‐workers in their Research Article (e202205111 ). The tailored polyelectrolyte has an anchoring effect and acts as a passivator for 2D perovskites, which can improve 2D perovskite phase alignment and interfacial charge transfer efficiency, and finally enables high‐efficiency and large‐area 2D perovskite solar cells.